Enabling federated emergencies and Public Safety Answering Points with wearable and mobile Internet of Things support: An approach based on EENA and OMA LWM2M emerging standards - Jara, Antonio J.; Bocchi, Yann; Genoud, Dominique; Thomas, Ian; Lambrinos, Lambros (My University, 2015)
We are witnessing the emergence of a new technology paradigm, one which focuses on the large scale integration and simplification of distributed technologies along with their fundamental realignment around the needs of people and society. The new Human Centric Intelligent Society results from these changes is connecting information from many different sources across the physical and virtual worlds, using the power of integration to achieve new insights and to enact change in ways which are quicker and more context aware than ever before. The Human Centric integration will lead to safer, more comfortable and more prosperous societies, but before arriving to this status, we have several challenges for the existing platforms to be migrated and digitalized into a common Cloud Computing ecosystem, and enable the common things with a Web of Things capabilities that can enable new forms of social infrastructure that react to the needs of people in real time. In this work, we present the contributions and extensions to the EENA Public Safety Answering Points standards and data structure (PIDFLO), in order to enable it with the capabilities to be integrated with data coming from personal and wearable sensors (Internet of Things). In details, we have extended PIDF-LO with the support of OMA LwM2M Web Objects, in order to offer a scalable and interoperable integration of the Internet of Things and the European Emergencies Services based on Open Standards.
Keywords: Bluetooth Smart; Cloud Computing; EENA; Emergencies; Federated; Internet of Things; IPv6; OMA; Smart Cities; Wearable Computing